A helyi pénzrendszerek közgazdasági és társadalmi elfogadottsága = The economical and social acceptance of the local currency systems - Varga, József (Közép-Európai Közlemények, 2018)
The purpose of my publication is to analyze the operation of local currency in Hungary from a macroeconomic point of view. First, I look at the general principles of issuing and running local money, and then the importance of local thinking. I would like to point out that one of the solutions to a series of globalized crises is the establishment of local money systems and then I exemine the role of the 2008 crisis in stimulating the creation of local money systems. According to my main point of view, the economic role of local money systems in Hungary is significant on theoretical level, but its effect is practically very small in the current domestic environment. The duality of the low interest rate environment and economic stability has led to a lack of economic climate for local money today. The major result of the local currency is the creation of an economic and legal environment in which the operation of transferable vouchers is more streamlined, thus it has become for the participating partners less risky.